Diseño y Control Predictivo de un Robot Colaborativo para Aplicaciones en Agricultura y Minería - Huayanay Villar, José Luis (2025)
This article presents the design, mathematical modeling and predictive control of a collaborative robot for applications in agriculture and mining. The robot for agriculture and mining being developed by the Villa Automation EIRL Company could have a significant impact on Peruvian society. The system consists of a robotic arm with servomotors and an ultrasonic sensor for the detection of objects and a four-wheeled chassis for its movement, an improved version of the “path tracking in mobile robotics powered by solar energy” project. A control based on the prediction of future error, similar to a PID, is implemented with the objective of optimizing performance in object manipulation. Experimental results and analysis of the robot's behavior in harvesting and drilling tasks are presented.